Distribución de las macrofitas en el Lago Yojoa, Honduras - Cruz, Gustavo Adolfo (1986)
The abundance, distribution and depth range of aquatic weeds were analized in Lake Yojoa, 31 aquatic angiosperms, 3 macro aIgae and 2 pteridophyts adapted to aquatic life were identified. Vallismeria sp., the submerged dominant species, has the widest distribution and greatest depth range. Heterogeneous distribution of certain emergent and floating species, between the North and South shores, seems to result from mechanical action of the prevalent North winds. The differences between the East and West shores are related to the topography, substrate, and forest cover. Lake Yojoa is eutrophic in nature with slight variations depending on the shore. The mechanical action of the winds detach and deposit the floating plant material, focussing the eutrofication on the South shore. The noxious aquatic weeds are not considered a threat in the lake especially to the hydroelectric plant on the North shore. The chemical and mechanical control of the aquatic weeds will destroy the optimal habitat of the food chain of Black Bus (Micropterus salmoides). Based on available data it is not considered prudent or necessary to introduce exotic fish or manatee, in order to control the aquatic weeds in the lake.